Investigating the use of reading strategies and its impact on reading comprehension among international students in a Malaysian public university - Chelster Sherralyn Jeoffrey Pudin (Global Academic Excellence, 2022)
The aim of this study is to determine the extent to which reading strategies and English language proficiency influence reading comprehension among Chinese undergraduates studying abroad. In addition, the study also aims to determine the reading difficulties encountered by these students and to identify the effective reading strategies they employed to improve their reading comprehension. The quantitative information gathered via a questionnaire and a reading test. The SPSS (descriptive analysis) results indicate that reading strategies and language proficiency jointly account for the variance in the students' test scores. In addition to informing scholarly practises of academic reading, this research contributes to the development and teaching of ESL curricula by highlighting the essential components of an effective ESL academic reading module.